How Useful Is a Linear Ozone Parameterization for Global Climate Modeling?. (3rd April 2020) - Meraner, Katharina; Rast, Sebastian; Schmidt, Hauke
Abstract: The explicit calculation of stratospheric ozone in global climate models still comes at a high computational cost. Here, the usefulness of a linear ozone parameterization in a global climate model is assessed by comparing it to an explicit chemistry scheme and to observations. It is shown that the annual mean total ozone column and the tropical ozone profile agree well for the linear and the explicit chemistry schemes and the observations. Ozone variability caused by the quasi‐biennial oscillation and by extratropical quasi‐stationary planetary waves is reproduced qualitatively, but its magnitude is underestimated in particular in the simulations using the linear parameterization. The response of ozone to a quadrupling of CO 2 simulated with both schemes is in the range of earlier simulations with explicit schemes. This concerns in particular ozone decreases in the tropical lower stratosphere and increases above predicted as a consequence of a strengthening of tropical upwelling and potentially affecting climate sensitivity. This study demonstrates that despite existing weaknesses a linear ozone parameterization can be a useful tool to represent stratospheric ozone in climate models at negligible computational cost. Plain Language Summary: Ozone is the main absorber of solar radiation in the stratosphere. Feedbacks between ozone, temperature, and circulation are therefore crucial for stratospheric variability and responses to external forcings like anthropogenic greenhouse gas emissions. However, the comprehensive representation of stratospheric ozone in global climate models comes at a high computational cost. Here, we analyze to what extent a computationally cheap linear ozone parameterization can overcome this problem. It is shown that a linear ozone scheme reproduces well key features of the mean ozone distribution but underestimates variability induced by circulation patterns like the quasi‐biennial oscillation of winds in the tropical stratosphere. The response of ozone to an idealized global warming scenario (instantaneous quadrupling of the atmospheric CO 2 concentration) simulated with the linear ozone scheme is in the range of earlier model studies with more complex chemistry schemes. We demonstrate that despite existing weaknesses, a linear ozone parameterization can be a useful tool to represent stratospheric ozone in climate models at negligible computational cost. Key Points: Linear scheme can be a useful tool to interactively represent ozone at low computational cost Responses of ozone to 4xCO 2 are very similar for an explicit and a linear ozone scheme Linear scheme underestimates amplitudes of circulation‐induced variability patterns